Implementation of Sustainable Evidence-Based Practice for the Assessment and Management of Pain in Residential Aged Care Facilities - Savvas, S.; Toye, Christine; Beattie, E.; Gibson, S. (W.B. Saunders Co., 2014)
Pain is common in residential aged care facilities (RACFs). In 2005, the Australian Pain Society developed 27 recommendations for good practice in the identification, assessment, and management of pain in these settings. This study aimed to address implementation of the standards and evaluate outcomes. Five facilities in Australia participated in a comprehensive evaluation of RACF pain practice and outcomes. Pre-existing pain management practices were compared with the 27 recommendations, before an evidence-based pain management program was introduced that included training and education for staff and revised in-house pain-management procedures. Post-implementation audits evaluated the program's success. Aged care staff teams also were assessed on their reports of self-efficacy in pain management. The results show that before the implementation program, the RACFs demonstrated full compliance on 6 to 12 standards. By the project's completion, RACFs demonstrated full compliance with 10 to 23 standards and major improvements toward compliance in the remaining standards. After implementation, the staff also reported better understanding of the standards (p < .001) or of facility pain management guidelines (p < .001), increased confidence in therapies for pain management (p < .001), and increased confidence in their training to assess pain (p < .001) and recognize pain in residents with dementia who are nonverbal (p = .003). The results show that improved evidence-based practice in RACFs can be achieved with appropriate training and education. Investing resources in the aged care workforce via this implementation program has shown improvements in staff self-efficacy and practice.